PERANAN KEPOLISIAN DALAM MENANGANI TINDAK PIDANA PELECEHAN SEKSUAL TERHADAP ANAK DI WILAYAH HUKUM KEPOLISIAN SEKTOR MANDAU-DURI - Diana, Ledy; ', Boentor; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
State has aspirations to realize peace and protection for its citizens. The statealso gives attention to the next generation so that the ideals of the nation can continue torun until the future. Kids are the future generation, which must be protected and beacknowledged, but as in the development and advancement of technology, crime evolved.One of them is the crime of sexual abuse committed against children. Sexual harassmentis a crime falling within the scope of lust. In this case the sexual abuse of children is acrime that is included in the scope of lust in which the victim is a child. In the case toprotect it formed the Police institution that aims to protect, shelter, and serve the public.The role of police is needed to be able to suppress the rate of development and combatingsexual abuse crimes committed against children.Sexual abuse crimes against children continues to increase, which in turn makeparents worry. The government then took steps to create new legislation that renews theold legislation, namely; Act 35 of 2014 on the